Vasculopathy associated with peripheral neuropathy in gait parameters of diabetic people - Mantovani, Alessandra Madia [UNESP] (2016)
Diabetic peripheral neuropathy (DPN) is a common complication of diabetes mellitus when glycemic levels are poorly controlled. Sometimes DPN is accompanied by vasculopathy (DPV), which can worsen the clinical prognosis. The aim of this study was to analyze the gait parameters of nondiabetic individuals and diabetic individuals with DPN with or without DPV.